Identification and Characterization of the Functional Elements within the Tobacco Etch Virus 5′ Leader Required for Cap-Independent Translation - Niepel, Mario (American Society for Microbiology, 1999)
Translation in plants is highly cap dependent, and the only plant mRNAs known to naturally lack a cap structure (m(7)GpppN) are viral in origin. The genomic RNA of tobacco etch virus (TEV), a potyvirus that belongs to the picornavirus superfamily, is a polyadenylated mRNA that is naturally uncapped and yet is a highly competitive mRNA during translation. The 143-nucleotide 5′ leader is responsible for conferring cap-independent translation even on reporter mRNAs. We have carried out a deletion analysis of the TEV 5′ leader to identify the elements responsible for its regulatory function and have identified two centrally located cap-independent regulatory elements (CIREs) that promote cap-independent translation. The introduction of a stable stem-loop structure upstream of each element demonstrated that CIRE-1 is less 5′ end dependent in function than CIRE-2. In a dicistronic mRNA, the presence of the TEV 5′ leader sequence in the intercistronic region increased expression of the second cistron, suggesting that the viral sequence can function in a 5′-distal position. Interestingly, the introduction of a stable stem-loop upstream of the TEV leader sequence or upstream of either CIRE in dicistronic constructs markedly increased their regulatory function. These data suggest that the TEV 5′ leader contains two elements that together promote internal initiation but that the function of one element, in particular, is facilitated by proximity to the 5′ end.